VII. Budapesti Nemzetközi Kisplasztikai Kiállitas. - Mücsarnok - Palace of Exhibitions, Budapest (Budapest : Ministery of Culture and Eduction Hungary, 1987)
Kienzer, Michael ; Pichler, Franz ; Troger, Gustav ; Weinberger, Lois ; Cardon, Eric ; Debliquy, Daniel ; Desmet, Etienne ; Roulin, Felix ; Deremendzsiev, Szpartak ; Ljutakov, Sztefan ; Prahov, Ljubomir ; Szimeonova, Sznezsana ; Palko, Mikulas ; Prokop, Stefan ; Ruzicka, Lubomir ; Vacek, Jaroslav ; Andersson, Thomas ; Forland, Berit ; Hoyer Hansen, Lone ; etc.
VII. Budapesti Nemzetközi Kisplasztikai Kiállitas / 7th International Small Sculpture Exhibition of Budapest, Mücsarnok - Palace of Exhibitions, Budapest, 3 September - 18 October 1987
boek